Challenges to Achieving Universal Health Coverage Throughout the World: A Systematic Review - Alireza Darrudi; Mohammad Hossein Ketabchi Khoonsari; Maryam Tajvar (Korean Society for Preventive Medicine, 2022)
Objectives No systematic review has explored the challenges related to worldwide universal health coverage (UHC). This study reviewed challenges on the road to UHC. Methods A systematic electronic search of all studies that identified the challenges of worldwide UHC was conducted, without any restrictions related to the publication date or language. A hand search and a bibliographic search were also conducted to identify which texts to include in this study. These sources and citations yielded a total of 2500 articles, only 26 of which met the inclusion criteria. Relevant data from these papers were extracted, summarized, grouped, and reported in tables. Results Of the 26 included studies, 7 (27%) were reviews, 6 (23%) were reports, and 13 (50%) had another type of study design. The publication dates of the included studies ranged from 2011 to 2020. Nine studies (35%) were published in 2019. Using the World Health Organization conceptual model, data on all of the challenges related to UHC in terms of the 4 functions of health systems (stewardship, creating resource, financing, and delivering services) were extracted from the included studies and reported. Conclusions This study provides a straightforward summary of previous studies that explored the challenges related to UHC and conducted an in-depth analysis of viable solutions.